The effect of applied stress on the crevice corrosion of 304 stainless steel in 3.5 wt% NaCl solution. (March 2022) - Zhu, L.Y.; Cui, Z.Y.; Cui, H.Z.; Wang, X.; Li, Y.Z.
Abstract: The effect of applied stress on the crevice corrosion of 304 stainless steel in 3.5 wt% solution is investigated. The delayed and immediate crevice corrosion of 304 stainless steel could occur under various applied stresses and different polarized potential. Both these two types of crevice corrosion are developed from the evolution of metastable pits. The lifetime of metastable pits is prolonged with the increased stress and the secondary metastable pit is observed under 400 MPa applied stress. This contributes to increased probability of metastable pits transiting to stable pits and then promotes crevice corrosion development with the increased stress. Highlights: Crevice corrosion of 304 stainless steel is developed from metastable pits. The concentration of defects in passive film increases with the increased stress. The applied stress could drastically extend the lifetime of metastable pits. Secondary metastable pit can be induced by applied plastic stress. Array reference electrodes can monitor evolution of metastable pit inside crevice.